Design a Smart Control Strategy to Implement an Intelligent Energy Safety and Management System - Jing-Min Wang; Ming-Ta Yang (International Journal of Distributed Sensor Networks)
The energy saving and electricity safety are today a cause for increasing concern for homes and buildings. Integrating the radio frequency identification (RFID) and ZigBee wireless sensor network (WSN) mature technologies, the paper designs a smart control strategy to implement an intelligent energy safety and management system (IESMS) which performs energy measuring, controlling, monitoring, and saving of the power outlet system. The presented RFID and billing module is used to identify user, activate smart power outlet (SPO) module, deduct payable for electricity, and cut off power supply to the outlets by taking away the RFID card. Further work on the SPO module, a control strategy based on the minimum effect and first-in first-out rule, is designed to autonomously shut down some of the power outlets instantly to prevent electrical circuit overload. In addition, the WSN transfers the power parameters of each SPO module to central energy monitoring platform, and the monitoring platform with graphical user interface (GUI) displays the real-time information and power charge of the electricity. Numerous tests validate the proposed IESMS and the effectiveness of the smart control strategy. The empirical findings may provide some valuable references for smart homes or smart buildings.